2019
DOI: 10.1186/s13048-019-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the benefits of neoadjuvant chemotherapy for advanced epithelial ovarian cancer: a retrospective study

Abstract: Objective To compare the chemoresistance and survival in patients with stage IIIC or IV epithelial ovarian cancer who were treated with neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) or primary debulking surgery (PDS). The clinical characteristics of patients who benefited from NACT were further evaluated. Methods We retrospectively analyzed 220 patients who underwent NACT followed by IDS or PDS from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
4
23
0
1
Order By: Relevance
“…For patients debulked to RD < 1 cm or to RD ≥ 1 cm after PDS, their prognosis had no significant differences. Moreover, after NACT, patients who were debulked to no RD after IDS had a significantly lower DFS and OS compared to patients with no RD after PDS [26]. These results agree with our results regarding the optimal debulking.…”
Section: Discussionsupporting
confidence: 91%
“…For patients debulked to RD < 1 cm or to RD ≥ 1 cm after PDS, their prognosis had no significant differences. Moreover, after NACT, patients who were debulked to no RD after IDS had a significantly lower DFS and OS compared to patients with no RD after PDS [26]. These results agree with our results regarding the optimal debulking.…”
Section: Discussionsupporting
confidence: 91%
“…Rauh-Hain and colleagues found that 88.8% of cases of recurrence in the NACT-IDS group were platinum resistant compared to 55.3% of cases in the PDS group (P = 0.001)27 . The same outcome was also found by Gao, who showed that 40.3% of patients in the NACT-IDS group and 23.1% in the PDS group experienced platinum-resistant recurrence and28 ; similarly, NACT induced chemotherapy resistance in cancer stem cell colonies29 . A limited number of studies have found that the TP53 gene mutation is the most common (70.3%) mutation after courses of NACT compared with before courses of NACT30 ; additionally, in platinum-resistant patients (relapsed within 6 months), the TP53 K351N mutation was significantly more severe in the NACT-IDS group than in the PDS group (57.14% vs 0%, P 0.01).…”
supporting
confidence: 79%
“…Some statistical data indicated that close to 70% of patients with OC remain undetected until the advanced stage [4]. Currently, the standard treatment for advanced OC is primary cytoreductive surgery followed by combination chemotherapy using platinum and taxane [4][5][6]. Tumour recurrence may ultimately occur in approximately 75% of patients with advanced OC, 20% of which becomes resistant [7].…”
Section: Introductionmentioning
confidence: 99%